Optimization of Samarinda City Parking Retribution Revenue Through e-Parking Innovation - Baren Sipayung (Formosa Journal of Multidisciplinary Research, 2022)
e-Parking is a parking service to realize safe, comfortable and transparent parking, which is expected to be able to launch progressive rates so that disputes between parking attendants and the community can be avoided. E-Parking is intended to reduce the practice of illegal parking attendants and retribution leakage can be overcome. The research method used is descriptive qualitative with interview, observation and documentation data collection techniques. To assess the effectiveness of E-Parking using Budiani's theory which includes the accuracy of program targets, program socialization, program objectives and monitoring. The results showed that the city government of Samarindah has succeeded in providing a tax service program to the government. There are also several program objectives that have been achieved because the accuracy of the target has been right where the target is the community, the Samarinda City Transportation Service and the Parking Interpreter. The monitoring of the program has been effective, followed by mentoring and evaluation of improvements that have been routinely carried out.